Field Calculator for sustainable rice production - CGIAR Research Program on Rice (2019)
Beta version of FC developed and shared with stakeholders for feedback. Assessment and discussion on fuller development incorporating this feedback is currently ongoing. Currently identifying service provider for next iterations, including CropIn/Buhler, Akvo, AgImpact, FarmForce, and Khethinext. Non-disclosure agreement (NDA) between IRRI and 2 contractors signed.